Visible Social Interactions Do Not Support the Development of False Belief Understanding in the Absence of Linguistic Input: Evidence from Deaf Adult Homesigners - Gagne, Deanna L.; Coppola, Marie (Frontiers in Psychology, 2017)
Congenitally deaf individuals exhibit enhanced visuospatial abilities relative to normally hearing individuals. An early example is the increased sensitivity of deaf signers to stimuli in the visual periphery (Neville & Lawson, 1987a). While these enhancements are robust and extend across a number of visual and spatial skill, they seem not to extend to other domains which could potentially build on these enhancements. For example, congenitally deaf children, in the absence of adequate language exposure and acquisition, do not develop typical social cognition skills as measured by traditional Theory of Mind tasks. These delays/deficits occur despite their presumed lifetime use of visuoperceptual abilities to infer the intentions and behaviors of others (e.g., O’Reilly, Peterson, & Wellman, 2014; Pyers & Senghas, 2009). In a series of studies, we explore the limits on the plasticity of visually-based socio-cognitive abilities, from perspective taking to Theory of Mind/False Belief, in rarely studied individuals: deaf adults who have not acquired a conventional language (Homesigners). We compared Homesigners’ performance to that of two other understudied groups in the same culture: Deaf signers of an emerging language (Cohort 1 of Nicaraguan Sign Language), and hearing speakers of Spanish with minimal schooling. We found that homesigners performed equivalently to both comparison groups with respect to several visual socio-cognitive abilities: Perspective Taking (Level 1 and Level 2), adapted from Masangkay et al. (1974), and the False Photograph task, adapted from Leslie & Thaiss (1992). However, a lifetime of visuo-perceptual experiences (observing the behavior and interactions of others) did not support success on False Belief tasks, even when linguistic demands are minimized. Participants in the comparison groups outperform the Homesigners, but did not universally pass the False Belief tasks. Our results suggest that while some of the social development achievements of young typically developing children may be dissociable from their linguistic experiences, language and/or educational experiences clearly scaffolds the transition into False Belief understanding. The lack of experience using a shared language cannot be overcome, even with the benefit of many years of observing others’ behaviors and the potential neural reorganization and visuospatial enhancements resulting from deafness.